Conocimiento de los estudiantes Universidad Antonio Nariño sede Bucaramanga de 6 a 10 semestre del año 2022 sobre el manejo del paciente diabético en odontología (2023)
The next study is of the observational cross-sectional type, it was carried out with the objective of acquiring information on the level of knowledge of students from sixth to tenth semester enrolled in the dental clinic of the Antonio Nariño university in the year 2022-2 on the management of diabetic patients, their classifications of the disease and the signs they manifest in their oral cavity, ; A non-probabilistic sampling of the voluntary type was carried out which is characterized by the student deciding to participate in the survey on a voluntary basis.